Social Media Campaigns on the @Rucas.Official Tiktok Platform in Creating Brand Awareness - Febriyana, Dhea; Yuniar; Nurfalah, Farida (Journal Research of Social Science, Economics, and Management, 2025)
Social media plays a strategic role in the digital era, especially in building brand awareness. In the context of increasingly competitive business, brand awareness is a crucial element that influences consumer preferences. To stay relevant and competitive, RUCAS implements a product differentiation strategy that not only establishes a strong brand image, but also offers unique values that are difficult for competitors to replicate. In Indonesia, the local fashion industry shows significant growth. This research aims to analyze RUCAS' social media campaign strategy on TikTok platform in building brand awareness. The research uses a descriptive qualitative approach with data triangulation techniques to explore how the uploaded content is able to build an emotional connection with the audience. This approach is based on interpretive theory, which emphasizes understanding subjective meanings from the informants' perspectives. Data collection was conducted through in-depth interviews with four main informants and one key informant, who were selected through purposive sampling technique. The results showed that the RUCAS social media campaign succeeded in attracting public attention and conveying social messages about diversity and equality. The campaign changed perceptions of marginalized groups and formed a new understanding of the importance of social awareness.